THE END OF THE AUTONOMY AND THE BEGINNING OF THE INDEPENDENCE MOVEMENT IN THE MIRROR OF THE JADID PRESS (Scientific journal of the Fergana State University, 2023)
The history of Turkestan Autonomy, its liquidation and the beginning of the armed movement against the Soviet regime are some of the interesting and relevant topics in the history of Uzbekistan. This article analyzes the matter in the periodical press of that time. The author expresses his opinion on those aspects of the history of the Autonomy of Turkestan and the armed movement against the Soviet regime that are well covered, as well as those that remain outside the point of view of the national press.